2003
DOI: 10.1002/elps.200305432
|View full text |Cite
|
Sign up to set email alerts
|

Improved separation of double‐stranded DNA fragments by capillary electrophoresis using poly(ethylene oxide) solution containing colloids

Abstract: The analysis of double-stranded (ds) DNA fragments by capillary electrophoresis (CE) using poly(ethylene oxide) (PEO) solution containing gold nanoparticles (GNPs) is presented, focusing on evaluating size dependence of the GNPs and PEO on resolution and speed. To prevent the interaction of the capillary wall with DNA, the capillary was dynamically coated with polyvinylpyrrolidone. Using different PEO solutions containing GNPs ranging in diameter from 3.5 to 56 nm, we have achieved reproducible, rapid, and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“…It was reported that SNPs would aggregate more seriously after adsorption on the bare glass surface than on the PVP-or PEO-coated glass [25], and the two-layer coating of PVP and PEO was found to be stable during electrophoresis [38]. In this work, the two-layer coating was formed by progressively flushing the capillary with 3% PVP solution, double-distilled water, and PEO-containing run buffer at pH 2.37 (under the .…”
Section: Wall Adsorption Of Snpsmentioning
confidence: 95%
“…It was reported that SNPs would aggregate more seriously after adsorption on the bare glass surface than on the PVP-or PEO-coated glass [25], and the two-layer coating of PVP and PEO was found to be stable during electrophoresis [38]. In this work, the two-layer coating was formed by progressively flushing the capillary with 3% PVP solution, double-distilled water, and PEO-containing run buffer at pH 2.37 (under the .…”
Section: Wall Adsorption Of Snpsmentioning
confidence: 95%
“…Functionalized gold nanoparticles bound to internal, modified sites of double stranded DNA were analyzed by Stevenson et al [36] using visible absorption spectrophotometry, gel electrophoresis, and atomic force microscopy. Huang et al [37] reported an improved separation of dsDNA fragments by capillary electrophoresis using poly(ethylene oxide) solution containing gold nanoparticles. They evaluated the size dependence of the gold nanoparticles and PEO on resolution and speed of separation and found that resolution and plate number of the solutes were doubled in the presence of the gold particles, probably due to changes in the observed mobility accrued from interactions of solutes with the particle surfaces.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…It usually takes a lot of time and effort, however, to test and develop a new polymer matrix [23]. Recently, addition of certain additives [22][23][24][25][26][27][28][29][30][31][32][33] into low-viscous polymer solutions has proved to be a very efficient and simple method to overcome the difficulty of filling capillaries and improve dsDNA separation performance, as described previously [34]. These examples indicate that the additives that promote chemical or physical cross-linking are required for good resolutions [32].…”
Section: Introductionmentioning
confidence: 97%
“…The choice of polymer has often been arbitrary and empirical [20], primarily because the mechanisms of DNA separation are not fully understood [3]; the details about mechanisms can be seen in the review [21]. Therefore, searching for low-viscosity polymer solutions with high sieving ability and self-coating ability still remains an important issue for high-throughput DNA analysis [22]. It usually takes a lot of time and effort, however, to test and develop a new polymer matrix [23].…”
Section: Introductionmentioning
confidence: 99%